The Bible or the church? - Anderson, Robert, 1841-1918 (London, UK Hodder and Stoughton, 1908)
Includes bibliographical references and index.
Brethren writer. Donated by the late Mr Thomas C. Denton.
Keywords: Church -- origins; Church -- relation to the Bible